2010
DOI: 10.1080/01496395.2010.507662
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Integrative Process for the Production of Bioactive Peptides from Whey by Proteolytic Commercial Mixtures

Abstract: The aim of this work is to develop an integrative process based on the use of an ion exchange resin for the enzymatic hydrolysis of b-lactoglobulin to produce peptides with angiotensin converting enzyme (ACE) inhibitory activity using whey as a feed stock. Unlike the conventional methods, the main advantage of this approach is that by integrating the selective separation of b-lactoglobulin from whey and its hydrolysis less complex mixtures of peptides are produced. Furthermore, peptides of similar charge as b-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
1
13
1
Order By: Relevance
“…Its application using sweet whey produced hydrolysates with potent 99 ACE-inhibitory activity with peptides derived from β-lactoglobulin and CMP. Furthermore, 100 Welderufael and Jauregi [31] demonstrated that the process require no purification or enrichment 101 step since hydrolysates produced were of high potency. The different composition of acid whey 102 as compared to sweet whey such as, high concentration of calcium and the absence of CMP in 103 acid whey could lead to hydrolysates of different composition and/or potency.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Its application using sweet whey produced hydrolysates with potent 99 ACE-inhibitory activity with peptides derived from β-lactoglobulin and CMP. Furthermore, 100 Welderufael and Jauregi [31] demonstrated that the process require no purification or enrichment 101 step since hydrolysates produced were of high potency. The different composition of acid whey 102 as compared to sweet whey such as, high concentration of calcium and the absence of CMP in 103 acid whey could lead to hydrolysates of different composition and/or potency.…”
mentioning
confidence: 98%
“…In our group, we have developed an integrative process combining ion exchange and 98 microfiltration [31,32]. Its application using sweet whey produced hydrolysates with potent 99 ACE-inhibitory activity with peptides derived from β-lactoglobulin and CMP.…”
mentioning
confidence: 99%
See 3 more Smart Citations